2020
DOI: 10.1590/1807-3107bor-2020.vol34.0044
|View full text |Cite
|
Sign up to set email alerts
|

Perceived vulnerability to Coronavirus infection: impact on dental practice

Abstract: SARS-CoV-2 is a new virus responsible for the outbreak of the respiratory disease COVID-19, which has spread to several countries around the world, causing considerable consternation and a fear of contagions in global healthcare settings. The objective of this study is to identify, among Madrid's adult population, the impact of COVID-19 on self-perceived vulnerability, infectiousness, aversion to germs, and other behaviors in the current situation regarding dental practice. This cross-sectional observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 26 publications
2
42
0
7
Order By: Relevance
“…Em um estudo recente, Gonzales-Olmo et al, 13 com dados da população de Madrid, demonstrou elevados níveis de auto-percepção individual de maior vulnerabilidade em relação à infecção pela COVID-19 ao procurar atendimento odontológico, considerado um serviço essencial de saúde. Assim, os pesquisadores observaram que a amostra de indivíduos com mais de 60 anos com doenças sistêmicas evitou o atendimento odontológico na maioria das vezes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em um estudo recente, Gonzales-Olmo et al, 13 com dados da população de Madrid, demonstrou elevados níveis de auto-percepção individual de maior vulnerabilidade em relação à infecção pela COVID-19 ao procurar atendimento odontológico, considerado um serviço essencial de saúde. Assim, os pesquisadores observaram que a amostra de indivíduos com mais de 60 anos com doenças sistêmicas evitou o atendimento odontológico na maioria das vezes.…”
Section: Discussionunclassified
“…Assim, os pesquisadores observaram que a amostra de indivíduos com mais de 60 anos com doenças sistêmicas evitou o atendimento odontológico na maioria das vezes. 13 …”
Section: Discussionunclassified
“…A survey with 669 dental practitioners from 30 countries [5] showed that 87% were afraid of getting infected with COVID-19 from patients or co-workers, and 90% felt anxious while treating patients who coughed or were suspected of COVID-19 infection. In contrast, a survey with general population in Spain [6] indicated that above 90% of respondents were not afraid of contracting COVID-19 at dental offices, nor would cancel a dental appointment. These differences in behavior could be related to factors including differences in local COVID-19 contraction and death rates, or even how local healthcare systems are managing the pandemic.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, a high number of patients have been canceling their previous appointments, 17 and others have perceived vulnerability to infection during dental practice. 24 A point often overlooked is the lack of inclusion of dental personnel in the public health emergency management system. In most countries, dentists do not participate in the direct care of patients infected with COVID-19.…”
Section: Impact Of Covid-19 Pandemic On the Dentist's Lifementioning
confidence: 99%